Cultivation of microalgae Nannochloropsis sp in chicken manure to increase biomass and lipids as an introduction to biodiesel production - Ayuzar, Eva; Mahdaliana, Mahdaliana; Khaidir, Khaidir; Fitria, Ade; Erlangga, Erlangga (Universitas Malikussaleh, 2022)
Microalgae is one of the natural resources that has the potential to make biodiesel because it contains a fairly high amount of oil. The content of fat (lipid) and fatty acid (fatty acid) in microalgae is a source of energy and is used as raw material for biodiesel. In lipids there are elements of saturated fatty acids that play a role in the process of making biodiesel. The addition of growth nutrients into microalgae culture media is considered the most influential aspect on the quantity of biomass produced by microalgae cultivation. This study aims to determine the effect of chicken manure on the growth rate of Nannochloropsis sp. and to get the best treatment the lipid content of Nannochloropsis sp. of dry weight. The method used in this study was to use a non-factorial Complete RandomIzed Design (RAL) with 3 repeat treatments. The treatments in this study were A: 0 mg/L, B: 250 mg/L, C: 300 mg/L, D: 350 mgL. The results showed that the effect of giving chicken manure with different doses had a very real effect on the density of Nannochloropsis sp, and population peaks. Treatment B with a dose of 250 mg/L of showed the best results with an average density value of 4713 x 104 cells/ml and a population peak of 9415 x 104 cells/ml and the highest lipid levels found in treatment B, which is 12.73. Water quality during the study was conditioned standard. Temperature 26 - 27 oC, pH 7.1 - 7.7, DO 5.2 - 6.3 and salinity 31 - 34 ppt. Based on the results of the study found that lipid results are high, so it is possible to try biodiesel testing.Keywords: Biodesel; Biomass; Lipid; Microalgae; Nannochloropsis sp